2007
DOI: 10.1111/j.1551-2916.2007.01822.x
|View full text |Cite
|
Sign up to set email alerts
|

Creep Behavior of Plasma‐Sprayed Zirconia Thermal Barrier Coatings

Abstract: Thermally sprayed ceramic coatings deposited from nanostructured feedstock powder have often demonstrated improved properties relative to coatings produced from conventional powders. This type of coating has been reported to exhibit better wear resistance and higher adhesion strength compared with conventional deposits. Powder consisting of hollow spherical particles has been reported to produce coating with lower unmelted particles and lower thermal conductivity. In this study, the thermo‐mechanical propertie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 22 publications
2
2
0
Order By: Relevance
“…These should be the results of both dislocation strengthening caused by previous C‐F tests and the protective effects of self‐healing coatings. Similar results were reported in previous work, 42 which mentioned that the healing of defects such as microcracks in the coating could significantly reduce the creep rate of the coating and substrate. Moreover, the coating structure remains relatively intact, and the spalling of the coating is hardly observed in the sample with 50% prior C‐F lifetime fraction.…”
Section: Resultssupporting
confidence: 91%
“…These should be the results of both dislocation strengthening caused by previous C‐F tests and the protective effects of self‐healing coatings. Similar results were reported in previous work, 42 which mentioned that the healing of defects such as microcracks in the coating could significantly reduce the creep rate of the coating and substrate. Moreover, the coating structure remains relatively intact, and the spalling of the coating is hardly observed in the sample with 50% prior C‐F lifetime fraction.…”
Section: Resultssupporting
confidence: 91%
“…Several experimental studies have revealed that the activation energy associated with the creep deformation of YSZ or Ni-YSZ at a temperature approximating that of SOFC operation (<1100 • C) was found to be in the range of 1.0-2.0 eV [5,54,55]. Laurencin et al suggested that these barriers characterized the surface diffusion of a cation, which was also consistent with our KMC simulations.…”
Section: Cation Diffusion At the Surfacesupporting
confidence: 88%
“…Such free-standing coatings allow measurements of properties that are difficult or rather impossible to determine with a substrate underneath. These measurements can be mechanical tests, e.g., for the evaluation of Young's modulus [1], bending strength [2], creep [3,4] or sintering properties [5][6][7], toughness [8], and crack propagation [9,10]. Additionally, functional properties like thermal diffusivity [11], optical properties [12], phase evolution [13], and attack by corrosive species as Calcium-Magnesium-Aluminum-Silicate (CMAS, [14]) are measured on free-standing coatings.…”
Section: Introductionmentioning
confidence: 99%